Quality Indicators of Self- Determination of Special Education Programs in Jordan - Jamil M. Smadi; Eman K. AL-Zboon (Sultan Qaboos University, 2014)
This study aimed to identify the level of commitment of special education programs in Jordan by means of qualitative indicators for self-determination. The sample consisted of 62 special education centers and institutions: 25 for intellectual disability, 15 for hearing disability, 10 for visual disability, and 12 for physical disability. To achieve the aim of the study, a self-determination scale of qualitative indicators was developed and an acceptable level of validity and reliability was derived before being applied to special education programs. The results revealed that special education programs that employ quality indicators of selfdetermination are at medium level. Also, at the medium level were the domains of staff, institution atmosphere, family, students' services, and physical environment. However, in the domains of individual educational programs, instructional strategies and self-evaluation, the level was low. The study proposed a set of recommendations based on the findings of the study.